Change during Psychotherapy through Sand Play Tray in Children That Have Been Sexually Abused - Tornero, María D. L. Angeles; Capella, Claudia (Frontiers in Psychology, 2017)
This paper presents the results of a qualitative study on the use of sandplay, or sand tray therapy, in the psychotherapeutic process of children who have been sexually abused. A longitudinal study was carried out with seven participants between the ages of 7 and 10 years old. Data was produced during observation of the therapeutic activity over the course of three different phases of treatment, using a rubric created especially for this observation. Three sandplay sessions were recorded: one at the start of therapy, one at the 3-month mark, and the third and final session after 6 months of treatment. Sessions were then transcribed for later analysis. A rubric was developed in order to help researchers identify central themes, behaviors and content of creative play, as well as the therapeutic relationship. Transcribed sessions and observation rubrics were evaluated using qualitative content analysis, and information was categorized according to verbal and behavioral characteristics of the game. Results of the present study reveal common and transversal forms of playful expression among this group of children shown by their engagement with sandplay. During this activity, participants elaborate personal stories that feature violence as a central theme, often involving aggression between two or more individuals. They also express their need for care and protection and work to resolve conflicts using fantasy. The shifting dynamics of sandplay at each stage of therapeutic treatment is an important finding that reveals the progress made during psychotherapy. In the third phase of treatment, sandplay encouraged movement among children, allowing them to act out meaningful scenarios and create structured situations with positive outcomes. Finally, the value of sandplay as an important therapeutic tool is discussed, primarily its role in supporting processes of change and allowing participants to assign new meanings to traumatic experiences. Its application to the field of clinical psychology, particularly when working with victims of sexual abuse, is also explored.